Penerapan Kurikulum Merdeka pada Pembelajaran IPAS Kelas V di SD Negeri 1 Selanegara - Dwiarini, Oktavia; Kurniawan, Alfi Muklis; Isnawati, Febri (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Learning based on the Merdeka Curriculum must be implemented in accordance with the provisions of the learning process with the principles of the Merdeka Curriculum. This study aims to describe how the Merdeka Curriculum is applied in IPAS learning for fifth grade at SD Negeri 1 Selanegara. This study uses a qualitative method with a case study approach. Data collection is carried out through observation, interviews, and documentation. The subjects of this research are the school principal, fifth-grade teacher, and five students selected based on certain criteria. The stages of data analysis are performed by reducing, presenting, and drawing conclusions. Based on the results of the data analysis, it shows that the implementation of the Merdeka Curriculum in learning IPAS for fifth grade at Selanegara Elementary School 1 goes through three main stages: planning, implementation, and assessment of learning. The planning focuses on learning objectives and teacher training, while the implementation uses lecture and group discussion methods, although differentiated learning has not been effective yet. The assessment includes formative, summative, and reflective assessments to improve the quality of learning. However, the implementation of this Merdeka Curriculum is not yet fully optimal due to existing issues and obstacles in its execution.